1992
DOI: 10.1152/jappl.1992.73.5.2105
|View full text |Cite
|
Sign up to set email alerts
|

Force-velocity shifts with repetitive isometric and isotonic contractions of canine gastrocnemius in situ

Abstract: The force-velocity (F-V) relationships of canine gastrocnemius-plantaris muscles at optimal muscle length in situ were studied before and after 10 min of repetitive isometric or isotonic tetanic contractions induced by electrical stimulation of the sciatic nerve (200-ms trains, 50 impulses/s, 1 contraction/s). F-V relationships and maximal velocity of shortening (Vmax) were determined by curve fitting with the Hill equation. Mean Vmax before fatigue was 3.8 +/- 0.2 (SE) average fiber lengths/s; mean maximal is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
3

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 0 publications
2
20
3
Order By: Relevance
“…However, in some cases, there is a clear indication of the break (2,21,28). A departure from the hyperbolic relationship has also been reported for isolated myosin (25) as well as for cardiac trabeculae (10).…”
Section: Discussionmentioning
confidence: 71%
“…However, in some cases, there is a clear indication of the break (2,21,28). A departure from the hyperbolic relationship has also been reported for isolated myosin (25) as well as for cardiac trabeculae (10).…”
Section: Discussionmentioning
confidence: 71%
“…This is illustrated in Fig. 4 Stainsby (1992). In the first four stuidies the maximum (unloaded) shortening selocity (VQ) Uvas measured; in the others, data points refer to malximtlnm shortening selocity (Wmax) extrapolated from force velocity (P-V) salues.…”
Section: Reduction Of Maximum Isometric Forcementioning
confidence: 95%
“…In general, mammalian muscle demonstrates very little curvature (a high a/Po ratio [2,9]). Ameredes et al [3] reported a/Po ratios of 1.0 to 1.6 for dog gastrocnemius-plantaris muscle in situ. Maximal velocity under the conditions of these experiments was similar to values previously reported for the rat medial gastrocnemius muscle under similar circumstances.…”
Section: General Force-velocity Propertiesmentioning
confidence: 96%